Remarkable high efficiency of red emitters using Eu(iii) ternary complexes. Issue 41 (4th May 2018) - Kalyakina, Alena S.; Utochnikova, Valentina V.; Zimmer, Manuel; Dietrich, Fabian; Kaczmarek, Anna M.; Van Deun, Rik; Vashchenko, Andrey A.; Goloveshkin, Alexander S.; Nieger, Martin; Gerhards, Markus; Schepers, Ute; Bräse, Stefan
Abstract : We have synthesized Eu(iii ) ternary complexes possessing record photoluminescence yields up to 90%. Abstract : We have synthesized Eu(iii ) ternary complexes possessing record photoluminescence yields up to 90%. This high luminescence performance resulted from the absence of quenching moieties in the Eu coordination environment and an efficient energy transfer between ligands, combined with a particular symmetry of the coordination environment.